Implementasi Pembaruan Data Statistik pada Sistem SIDOK-Site sebagai Upaya Mendukung Pelayanan Informasi Publik BPS Kabupaten Sukabumi - Rifka Salsabila Firdaus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
Statistical data updating is an essential effort to support public information transparency by providing accurate, up-to-date, and accessible statistical information. This activity aimed to implement statistical data updating through the SIDOK-Site system at the Central Statistics Agency (BPS) of Sukabumi Regency to improve public information services. The implementation method consisted of data identification, collection from official sources, validation, data compilation, updating within the SIDOK-Site system, and verification before publication on the official BPS website. Data were obtained through observation, documentation, and official publications, including Sukabumi Regency in Figures, People's Welfare Statistics, and other statistical reports. The updating process covered population, social and welfare, economy and trade, agriculture, and geography and regional data categories. Each category was updated using the latest statistical information while ensuring consistency, proper formatting, and data validity. The results showed that the updating process improved the consistency, accuracy, and timeliness of statistical information available on the BPS Sukabumi Regency website. Furthermore, this activity enhanced competencies in managing statistical data through information systems. Regular data updating supported by effective validation and verification is essential for maintaining data quality and supporting evidence-based decision-making in various development sectors